The dialogic space offered by curriculum-making in the process of learning to teach, and the creation of a progressive knowledge-led curriculum - Lambert, David; Biddulph, Mary (Asia-Pacific journal of teacher education, 2015)
There is widespread system response to the perceived needs of education for twenty-first century, where learning-to-learn is privileged and schools are organised to prepare young people for work. One casualty of such skills-led teaching is deep thinking about curriculum questions and the knowledge contents of teaching in relation to the needs, motivations and experiential knowledge of students. In this paper we argue for greater conceptual clarity between curriculum and pedagogy, and between the worlds of children's experience and disciplinary knowledge, in order to deepen teachers' understanding of the practice of teaching. The paper shows how using the conceptual tools of curriculum making is key to becoming, and developing as a teacher. This paper supports subject specialism in teaching in a manner that respects the social and cultural capital of young people and their role in knowledge creation together with the emancipatory significance of gaining epistemic access to disciplinary knowledge.